Transformasi Kepemimpinan Religius di Pesantren Nahdlatut Ta’limiyah Pamekasan - Darain, A Sa'dud; Nurhadi, Ali; Mubarok, A. Khuzainol; Sofyan, Achmad; Anshari, Achmad (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study examines the transformation of religious leadership in improving the quality of superior education at Pondok Pesantren Nahdlatut Ta’limiyah Pamekasan. The background of this research is based on the importance of leadership innovation in responding to global challenges and modernization in Islamic education. This research uses a qualitative approach with a case study method through participatory observation, in-depth interviews, and documentation. The results of the study show that the model of religious leadership in this pesantren has undergone a significant transformation from a traditional charismatic pattern to a participatory and modern managerial model that remains rooted in Islamic spiritual values. The leadership strategies implemented include curriculum reform based on the integration of religious and general sciences, institutional management optimization, and the digitalization of administrative systems. The pesantren leaders have also succeeded in developing a progressive academic culture and excellent student character through a holistic approach, exemplary leadership, and innovative learning methods. The commitment to providing free education for more than 2,000 students reflects an inclusive and socially oriented leadership value. The real impact of these strategies can be seen in the improved academic achievements of students, the increasing competitiveness of graduates, and the growing public trust in the quality of the pesantren’s education. This study recommends the implementation of a transformative religious leadership model as a solution for improving the quality of Islamic education in pesantren-based institutions in Indonesia